PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN FAKULTAS TEKNOLOGI INDUSTRI UNIVERSITAS TRISAKTI - Ari Nur Yahya (Jurnal Ekonomi Bisnis Indonesia, 2022)
This study aims to determine the effect of work environment, motivation and career development on employee performance. This study uses primary data obtained from questionnaires distributed from respondents who are employees of the Faculty of Industrial Technology, Trisakti University. The questionnaires distributed were 60 questionnaires and filled out well by the respondents who were processed using the statistical software SPSS 21.0 for Windows to test the validity, reliability, multicollinearity, heteroscedasticity, autocorrelation, multiple linear regression, T test, F test and coefficient of determination test to determine the effect of each variable. It is concluded that together the work environment (X1), motivation (X2) and career development (X3) affect employee performance (Y). The correlation coefficient value (R) is 0.910, which means that the variables of work environment, motivation, and career development have a very strong relationship with employee performance variables. The value of the coefficient of determination adjusted R square is 0.819 or 81.9%. This shows that the contribution of the independent variables (work environment, motivation and career development) to the dependent variable (employee performance) is 81.9%. While the remaining 18.1% is influenced by other variables that are not disclosed in this study.